Human Thinking and Language, Their Interrelation: A Theoretical Analysis within the Framework of Cognitive and General Linguistics - Xikmatullayeva, Mohichexra Latifjon qizi (The Lingua Spectrum, 2026)
This article analyzes the relationship between language and thinking from the perspectives of general and cognitive linguistics. The role of language in the formation, preservation, and transmission of knowledge in human consciousness is highlighted. Furthermore, the stages of studying the relationship between language and thinking, cognitive processes, and the inseparable connection between thinking and language are revealed on the basis of scientific sources. During the research, descriptive, comparative, and cognitive analysis methods are employed. In addition, it is noted that language and thinking have been studied not only in modern times but also throughout history by our great ancestors. The main purpose of the study is to comparatively and theoretically analyze the study of the relationship between language and thinking in general and cognitive linguistics. The article summarizes the views on language and thinking expressed by foreign scholars such as Wilhelm von Humboldt, Edward Sapir, and Benjamin Lee Whorf, as well as great Uzbek thinkers Alisher Navoi and Ibn Sina, together with the representative of modern cognitive linguistics Sh. Safarov. This research briefly concludes how scholars have studied the relationship between language and thinking in general and cognitive linguistics.